Vulvar reconstruction with a lotus petal flap in recurrent vulvar carcinoma: a case report - Bhagat, Birendra; Jaiswal, Swati; C., Sabina K.; Gupta, Sumedha (International Journal of Research in Medical Sciences, 2026)
Vulvar cancer is an uncommon gynecologic malignancy with a significant risk of local recurrence following surgical treatment. Management of recurrent disease often requires wide local excision, resulting in extensive soft-tissue defects that pose reconstructive challenges. We report the case of a 61-year-old woman with recurrent vulvar squamous cell carcinoma who underwent wide local excision followed by immediate vulvar reconstruction using a lotus petal musculocutaneous flap. The postoperative course was complicated by partial flap necrosis, which was managed conservatively with satisfactory healing. Histopathology confirmed tumor-free margins, and adjuvant radiotherapy was planned due to close margins and recurrent disease. This case highlights the reliability, versatility, and functional benefits of the lotus petal flap in reconstructing complex vulvar defects after radical excision in recurrent vulvar carcinoma.